Fluted-point technology in Neolithic Arabia: An independent invention far from the Americas - Crassard, Rémy; Charpentier, Vincent; McCorriston, Joy; Vosges, Jérémie; Bouzid, Sofiane; Petraglia, Michael D. (PLOS ONE, 2020)
New World archaeologists have amply demonstrated that fluted point technology is specific to Terminal Pleistocene American cultures. Base-fluted, and rarer tip-fluted, projectile points from the Americas have been well-documented by archaeologists for nearly a century. Fluting is an iconic stone tool manufacturing method and a specific action that involves the extraction of a channel flake along the longitudinal axis of a bifacial piece. Here we report and synthesize information from Neolithic sites in southern Arabia, demonstrating the presence of fluting on a variety of stone tool types including projectile points. Fluted projectile points are known from both surface sites and stratified contexts in southern Arabia. Fluting technology has been clearly identified at the Manayzah site (Yemen) dating to 8000–7700 cal. BP. Examination of fluted points and channel flakes from southern Arabia enable a reconstruction of stone tool manufacturing techniques and reduction sequences (chaines opératoires). To illustrate the technological similarities and contrasts of fluting methods in Arabia and the Americas, comparative studies and experiments were conducted. Similarities in manufacturing approaches were observed on the fluting scars of bifacial pieces, whereas technological differences are apparent in the nature and localization of the flute and, most probably, the functional objective of fluting in economic, social and cultural contexts. Arabian and American fluted point technologies provide an excellent example of convergence of highly specialized stone tool production methods. Our description of Arabian and American fluting technology demonstrates that similar innovations and inventions were developed under different circumstances, and that highly-skilled and convergent production methods can have different anthropological implications.